A new model for coal gasification on pressurized bubbling fluidized bed gasifiers. (15th October 2016) - Sánchez, Cristian; Arenas, Erika; Chejne, Farid; Londoño, Carlos A.; Cisneros, Sebastian; Quintana, Juan C.
Highlights: A new model was proposed for the simulation of fluidized bed reactors. The model was validated against experimental data found in the literature. The model was compared and found to be superior to other models reported in the literature. Effects of pressure, temperature, steam/coal and air/coal ratios over gas composition were studied. Abstract: Many industries have taken interest in the use of coal gasification for the production of chemicals and fuels. This gasification can be carried out inside a fluidized bed reactor. This non-ideal reactor is difficult to predict due to the complex physical phenomena and the different chemical changes that the feedstock undergoes. The lack of a good model to simulate the reactor's behavior produces less efficient processes and plant designs. Various approaches to the proper simulation of such reactor have been proposed. In this paper, a new model is developed for the simulation of a pressurized bubbling fluidized bed (PBFB) gasifier that rigorously models the physical phenomena and the chemical changes of the feedstock inside the reactor. In the model, the reactor is divided into three sections; devolatilization, volatile reactions and combustion-gasification. The simulation is validated against experimental data reported in the literature and compared with other models proposed by different authors; once the model is validated, the dependence of the syngas composition on operational pressure, temperature, steam/coal and air/coal ratios are studied. The results of this article show how this model satisfactorily predicts the performance of PBFB gasifiers.